Making deep immunophenotyping accessible: the successful application of a guided 23-parameter mouse immunophenotyping panel package provided through a shared resource - Isbell, Madison G.; Wendling, Alex; Pei, Xinyan; Kumar, Amit; Mannangatti, Padmanabhan; Krisanits, Bradley A.; Cheatham, Stanley; Michenkova, Marie; Shumilov, Kirill; Mendoza, Rachel G.; Fernandez, Matthew E.; Bryan, Allyn; et al. (Frontiers in Immunology, 2026)
This 23-color mouse immunophenotyping panel was designed and developed by the Virginia Commonwealth University’s (VCU) flow cytometry shared resource (FCSR) to easily bring new use to our high-parameter spectral cytometers. Our method is broadly applicable to multiple tissue types, is modifiable, and provides a reproducible, cost-effective option for utilizing high-parameter flow cytometry. To facilitate the mouse immunophenotyping panel, researchers can be provided with optimized reagents, a step-by-step staining protocol, instrument training, pre-run single-color controls, and acquisition and analysis templates to streamline the workflow. Data analysis is generally done with a traditional manual gating strategy, but t-stochastic neighbor embedding (tSNE) and uniform manifold approximation projection (uMAP) generation can be performed, as desired. In an FCSR, this panel requires only light preparation work for shared resource (SR) staff with maximum benefit for researchers. Overall, this publication describes how SR facilities can provide additional benefits and services to their clientele by reducing costs, increasing reproducibility, and lowering the barriers of entry for researchers into the field of high parameter spectral flow cytometry. The panel described is used as an example of the application of the included methods, as well as a complete resource for other institutions to utilize themselves.